Consensus for the diagnosis, prognosis and treatment of canine mammary tumors - Cassali, Geovanni D.; Lavalle, Gleidice E.; Nardi, Andrigo B. de; Ferreira, Enio; Bertagnolli, Angélica C.; Estrela-Lima, Alessandra; Alessi, Antonio C. [UNESP]; Daleck, Carlos R. [UNESP]; Salgado, Breno S. [UNESP]; Fernandes, Cristina G.; Sobral, Renata A.; Amorim, Renée Laufer [UNESP]; et al. (My University, 2011)
The purpose of this paper is to establish criteria that could guide the diagnosis, prognosis and treatment of canine mammary neoplasias. It was elaborated during the Mammary Pathology Meeting: Diagnosis, Prognosis and Treatment of the Canine Mammary Neoplasm, held on November 6 th and 7 th, 2010 in Belo Horizonte - MG, Brazil, sponsored by the Laboratory of Comparative Pathology - UFMG, with the support of the Brazilian Association of Veterinary Pathology (ABPV) and Brazilian Association of Veterinary Oncology (ABROVET). Academics from several regions of Brazil were present and contributed to this work.
Keywords: Animal; Dogs; Mammary neoplasms; Medical oncology; Animalia; Canis familiaris